Pengaruh Dukungan Sosial dengan Kualitas Hidup pada Penderita Human Immunodeficiency Virus (HIV) - Istiqomah, Anisa Cahyanti; Kurniati, Mala; Yanti, Dhiny Easter; Febriani, Christin Angelina; Samino, Samino (Universitas Malahayati, 2025)
ABSTRACT It is crucial for people living with HIV/AIDS to pay attention to aspects of their quality of life because HIV/AIDS is a chronic and progressive condition, impacting all facets of life—physical, psychological, social, and spiritual. One significant factor influencing a person's quality of life is family support. This study aims to determine the influence of social support on the quality of life of people living with HIV in Mataram Baru Regency, Lampung Timur. This quantitative study employs a cross-sectional approach. The population for this study comprises all cases in Mataram Baru Regency, Lampung Timur in October 2022, totaling 89 people using a total sampling technique, namely the entire total population. Data were collected using a questionnaire. Data analysis was performed using univariate analysis, bivariate analysis (Chi-Square Test), and multivariate analysis (multiple logistic regression). The results showed that 60,7% of participants reported a good quality of life, 68,5% received emotional support, 58,4% received informational support, and 52,8% did not receive material support. There was a significant relationship between emotional support (p-value = 0,001, OR = 7,9) and material support (p-value = 0,029, OR = 1,9) with quality of life. However, there was no significant relationship between informational support and quality of life (P-value = 0,194). Emotional support emerged as the dominant factor in this study, with the highest odds ratio (OR = 12,981). It is recommended that families provide support to family member living with HIV, such as by participating in activities held by the community of people living with HIV, to foster emotional closeness. Keywords: Quality of Life, Social Support, People Living with HIV ABSTRAK Orang dengan HIV/AIDS sangat penting untuk memperhatikan aspek kualitas hidupnya karena HIV/AIDS bersifat kronis dan progresif, sehingga berdampak luas pada segala aspek kehidupan baik fisik, psikologis, sosial, maupun spiritual. Salah satu faktor yang mendukung dimensi pada kualitas hidup seseorang adalah dukungan keluarga. Tujuan penelitian ini untuk mengetahui pengaruh dukungan sosial dengan kualitas hidup pada penderita HIV di Kecamatan Mataram Baru Lampung Timur. Jenis penelitian kuantitatif pendekatan Cross Sectional. Populasi dalam penelitian ini adalah seluruh kasus di Kecamatan Mataram Baru Lampung Timur bulan Oktober 2022 sebanyak 89 orang dengan teknik sampling total sampling yaitu seluruh total populasi. Pengumpulan data menggunakan kuesioner analisis data dengan univariat, bivariat (Uji Chi Square), multivariat regresi logistik ganda. Hasil didapatkan kualitas hidup baik sebanyak 60,7%, dukungan emosional mendukung sebanyak 68,5%, informasi mendukung sebanyak 58,4%, dan dukungan materi tidak mendukung sebanyak 52,8%. Ada hubungan dukungan emosional (p-value = 0,001 OR 7,9) dan dukungan materi (p-value = 0,029 OR 1,9) dengan kualitas hidup pada penderita HIV dan tidak ada hubungan dukungan informasi dengan kualitas hidup pada penderita HIVdengan nilai (p-value = 0,194) serta faktor yang dominan dalam penelitian dalam penelitian ini adalah dukungan emosional, dimana memiliki nilai OR tertinggi yaitu sebesar 12.98. Saran bagi keluarga diharapkan keluarga dapat memberikan dukungan kepada penderita HIV seperti ikut serta dalam kegiatan yang diadakan oleh komunitas penderita HIV sehingga terjalin kedekatan emosional yang semakin erat. Kata Kunci: Kualitas Hidup, Dukungan Sosial, Penderita HIV